Constructing functional cuticles: analysis of relationships between cuticle lipid composition, ultrastructure and water barrier function in developing adult maize leaves. (21st October 2019) - Bourgault, Richard; Matschi, Susanne; Vasquez, Miguel; Qiao, Pengfei; Sonntag, Annika; Charlebois, Caleb; Mohammadi, Marc; Scanlon, Michael J; Smith, Laurie G; Molina, Isabel
Abstract: Background and Aims: Prior work has examined cuticle function, composition and ultrastructure in many plant species, but much remains to be learned about how these features are related. This study aims to elucidate relationships between these features via analysis of cuticle development in adult maize ( Zea mays L.) leaves, while also providing the most comprehensive investigation to date of the composition and ultrastructure of adult leaf cuticles in this important crop plant. Methods: We examined water permeability, wax and cutin composition via gas chromatography, and ultrastructure via transmission electron microscopy, along the developmental gradient of partially expanded adult maize leaves, and analysed the relationships between these features. Key Results: The water barrier property of the adult maize leaf cuticle is acquired at the cessation of cell expansion. Wax types and chain lengths accumulate asynchronously over the course of development, while overall wax load does not vary. Cutin begins to accumulate prior to establishment of the water barrier and continues thereafter. Ultrastructurally, pavement cell cuticles consist of an epicuticular layer, and a thin cuticle proper that acquires an inner, osmiophilic layer during development. Conclusions: Cuticular waxes of the adult maize leaf are dominated by alkanes and alkyl esters. Unexpectedly, these are localized mainly in the epicuticular layer. Establishment of the water barrier during development coincides with a switch from alkanes to esters as the major wax type, and the emergence of an osmiophilic (likely cutin-rich) layer of the cuticle proper. Thus, alkyl esters and the deposition of the cutin polyester are implicated as key components of the water barrier property of adult maize leaf cuticles.